Trade union awareness and understanding among non-academic employees - Ismail, Fadillah; Chong, Tan Han (Journal of Islamic, Social, Economics and Development, 2026)
Trade unions provide collective representation that safeguards workers’ rights and welfare, including within higher education institutions where non-academic employees sustain daily operations. However, available evidence indicates that union awareness and understanding among university support staff in Malaysia remain low, reflected in limited knowledge of union roles, functions, and membership benefits. Using a focused literature-based synthesis, this paper consolidates core dimensions of union awareness and knowledge and identifies recurrent constraints that weaken engagement—most notably underexposure to union activities, negative perceptions toward unionism, and inadequate rights consciousness, alongside pressing work realities such as heavy workload and career insecurity. The discussion further underscores the heightened relevance of strengthening union literacy in the post-pandemic context and advances strategic directions to revitalise participation through modernised union practices, structured awareness initiatives, and more accessible communication pathways that support resilient labour representation in Malaysian universities.